“Gereja untuk Tuhan, Compang untuk Leluhur” Sebuah Sintesis Reflektif di Wae Rebo - Bambang Purnama Putra (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines the dialogical encounter between Manggarai local spirituality and Catholic theology within the lived faith practices of the Wae Rebo indigenous community in West Flores. Employing a contextual theological approach and cultural hermeneutics, this study highlights how compang rituals, Catholic liturgy, and everyday magi practices do not function as mutually exclusive systems but rather as a reflective synthesis continuously negotiated in social and spiritual life. A micro-ethnography was conducted in April 2025 through participant observation, in-depth interviews, and visual documentation. The findings reveal that Catholicism operates as a moral–liturgical infrastructure, the compang serves as the cosmological center of analogism, and magi functions as an epistemology of care that regulates the relational balance between humans, nature, and ancestors. Together, these dimensions constitute a reflective synthesis that adapts to the pressures of modernity and tourism while maintaining the ontological sovereignty of the indigenous community. This study enriches the understanding of faith inculturation and religious pluralism in Indonesia and demonstrates that local spirituality can serve as a participatory and dynamic theological space amid social transformation.